White Matter Integrity and Treatment-Based Change in Speech Performance in Minimally Verbal Children with Autism Spectrum Disorder - Chenausky, Karen; Kernbach, Julius; Norton, Andrea; Schlaug, Gottfried (Frontiers in Human Neuroscience, 2017)
We investigated the relationship between imaging variables for two language/speech-motor tracts and speech fluency variables in ten minimally verbal (MV) children with autism. Specifically, we tested whether measures of white matter integrity - fractional anisotropy (FA) of the arcuate fasciculus (AF) and frontal aslant tract (FAT) - were related to change in percent syllable-initial consonants correct, percent prompts responded to, and percent syllable insertion errors (from best baseline to post 25 treatment sessions). 23 minimally verbal children with ASD received Auditory-Motor Mapping Training (AMMT), an intonation-based treatment to improve fluency in spoken output, and we report on seven who received a matched control treatment. Ten of the AMMT participants were able to undergo a magnetic resonance imaging study at baseline; their performance on baseline speech production measures is compared to that of the other two groups. No baseline differences were found between groups. A canonical correlation analysis (CCA) relating FA values for left- and right-hemisphere AF and FAT to speech production measures showed that FA of the left AF and right FAT were the largest contributors to the synthetic independent imaging-related variable. Change in percent syllable-initial consonants correct and percent syllable-insertion errors were the largest contributors to the synthetic dependent fluency-related variable. Regression analyses showed that FA values in left AF significantly predicted change in percent syllable-initial consonants correct, no FA variables significantly predicted change in percent items responded to, and FA of right FAT significantly predicted change in percent syllable-insertion errors. Results are consistent with previously identified roles for the AF in mediating bidirectional mapping between articulation and acoustics, and the FAT in its relationship to speech initiation and fluency. They further suggest a division of labor between the hemispheres, implicating the left hemisphere in accuracy of speech production and the right hemisphere in fluency in this population. Changes in response rate are interpreted as stemming from factors other than the integrity of these two fiber tracts. This study is the first to document the existence of a subgroup of minimally verbal children who experience increases in syllable- insertion errors as their speech develops in response to therapy.